Reinsurance as Capital Optimization Tool under Solvency II - Gurenko, Eugene N.; Itigin, Alexander (World Bank, Washington, DC, 2013)
This paper compares solvency capital requirements under Solvency I and Solvency II for a sample mid-size insurance portfolio. According to the results of a study, changing the solvency capital regime from Solvency I to Solvency II will lead to a substantial additional solvency capital requirement that might represent a heavy burden for the company's shareholders. One way to reduce the capital requirement under Solvency II is to increase reinsurance protection, which will reduce the net retained risk exposure and hence also the solvency capital requirement. Therefore, this paper proposes an extended reinsurance structure that, under Solvency II, brings the capital requirement back to the level of that required under Solvency I. In a step-by-step approach, the paper demonstrates the extent of solvency relief attained by the insurer by applying different possible adjustments in the reinsurance structure. To evaluate the efficiency of reinsurance as the solvency capital relief instrument, the authors introduce a cost-of-capital based approach, which puts the achieved capital relief in relation to the costs of extending the reinsurance protection. This approach allows a direct comparison of reinsurance as a capital relief instrument with debt instruments available in the capital market. With the help of the introduced approach, the authors show that the best capital relief efficiency under all examined reinsurance alternatives is achieved when a financial quota share contract is chosen for proportional reinsurance.